2010
DOI: 10.1111/j.1365-2443.2009.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for Dnmt3a‐dependent imprinting during oocyte growth obtained by conditional knockout with Zp3‐Cre and complete exclusion of Dnmt3b by chimera formation

Abstract: In the male and female germ-lines of mice, both of the two de novo DNA methyltransferases Dnmt3a and Dnmt3b are expressed. By the conditional knockout experiments using the TnapCre gene, we previously showed that deletion of Dnmt3a in primordial germ cells disrupts paternal and maternal imprinting, however, Dnmt3b mutants did not show any defect. Here, we have knocked out Dnmt3a after birth in growing oocytes by using the Zp3-Cre gene and obtained genetic evidence that de novo methylation by Dnmt3a during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 55 publications
5
69
0
Order By: Relevance
“…57,58 DNA methyltransferases A (DNMT3A) and its cofactor DNA methyltransferases L (DNMT3L) are required to establish DNA methylation in growing oocytes. 59 Maternalspecific de novo DNA methylation likely contributes to gene regulation in the oocyte and marks specific genes for activity in the embryo, as in the case of imprinted genes. 60 Indeed, Hdac1/2 mutant oocytes fail to establish normal imprinting DNA methylation marks.…”
Section: Hdac2 Regulates Global Dna Methylation and Genomic Imprintinmentioning
confidence: 99%
“…57,58 DNA methyltransferases A (DNMT3A) and its cofactor DNA methyltransferases L (DNMT3L) are required to establish DNA methylation in growing oocytes. 59 Maternalspecific de novo DNA methylation likely contributes to gene regulation in the oocyte and marks specific genes for activity in the embryo, as in the case of imprinted genes. 60 Indeed, Hdac1/2 mutant oocytes fail to establish normal imprinting DNA methylation marks.…”
Section: Hdac2 Regulates Global Dna Methylation and Genomic Imprintinmentioning
confidence: 99%
“…[20][21][22] This enzyme forms a complex with the structurally related, germ-cell-specific cofactor Dnmt3L, which enhances the catalytic activity of Dnmt3a and is important for imprint establishment (Figure 1). 21,[23][24][25] The other de novo methyltransferase Dnmt3b is not involved, except at one particular ICR (see later).…”
mentioning
confidence: 99%
“…It was later confirmed that the mutant oocytes indeed lack DNA methylation at these germline DMRs [39]. It was also established that DNMT3B is dispensable for the establishment of the maternal imprints [39].…”
Section: Mechanism Of Imprint Establishment In Male and Female Germ Cmentioning
confidence: 58%
“…In these studies, embryos derived from the mutant oocytes displayed loss of DNA methylation at the maternal alleles of the DMRs that are normally maternally methylated, and biallelic expression or silencing of the imprinted genes associated with these DMRs [36][37][38][39]. It was later confirmed that the mutant oocytes indeed lack DNA methylation at these germline DMRs [39]. It was also established that DNMT3B is dispensable for the establishment of the maternal imprints [39].…”
Section: Mechanism Of Imprint Establishment In Male and Female Germ Cmentioning
confidence: 66%
See 1 more Smart Citation